Research Output Analysis of Landfill Gas: A Global Perspective - Liu, Yong; Yang, Lie; Chen, Zhulei; Wang, Jia (Asian Journal of Chemistry, 2015)
Landfill gas is a by-product of landfilling municipal solid waste and contributes to greenhouse effect. The paper analyzed the growth and development of landfill gas research productivity in the world for the period 1997-2012. All authors from 652 institutions contributed 649 publications out of which 592 were journal articles (including 52 proceeding papers), 23 reviews, 14 new items, 8 editorial materials, 5 letters, 5 meeting abstract, 1 correction and 1 reprint. About 4.47 % of publications were contributed by Technical University of Denmark, followed by North Carolina State University (2.16 %) and University of Calgary (2.16 %). Leading 20 authors in the area published at least 5 articles per person. An analysis of the title-words showed that "waste", "methane" and "emissions"were recent major topics of landfill gas research in the world. The results could help researchers understand the characteristics of research output and search hot spots of landfill gas field.